Flexural Strength and Behavior of Flat Steel Plate-Concrete Composite Beams - Hassan, Kawan Mohammed; Saeed, Jalal Ahmed (Sulaimani Journal for Engineering Sciences, 2023)
Steel rebar’s are widely used as main flexural reinforcement in reinforced concrete beams. It’s quite attractive to explore the use of another type of material for this purpose. This study aims to investigate the flexural behavior of reinforced concrete beams using steel checker plates instead of traditional steel rebar’s. In this study fourteen simply supported beams where cast and tested under two-point loads. All the beams had the same steel reinforcement and the dimensions of 2000 mm in length, 250 mm in height and 200mm in width, twelve specimens of these beams were reinforced by horizontal and vertical checker steel plates having total thickness (12mm) with different arrangements and end anchorages. Two of these specimen beams were control beams reinforced with rebar’s. The main variables of the research arrangement, number and anchorage of steel checker plates. Based on the experimental results it found that there is a reduction in crack load and ultimate load of composite steel checker plate beams as compared to reinforced beams. In contrast there was observed increment in ductility of checker steel plate beams compared with beam reinforced with normal rebar’s, while in different arrangements (vertical and horizontal) of steel plates, with same cross sectional area when the number of checker plates increased the load also increased by 14% 12% and 8% also 11%, 23% and 27% for both cracking and ultimate loads respectively. Also the deflection of steel checker plate beams after failure was more than steel bars
Keywords: Reinforced Concrete Beam; Composite Beams; Checker steel plate; Flexural Strength; Ductility; Deformation